School Grammar in the Early Chilean Educational System: Field, Agents, and Control (1846-1865) - Cifuentes Sandoval, Juan (2025)
This research contributes to the historical study of school grammar in Chile from a perspective that links metalinguistic codification with the dynamics of collaboration and competition within the fields (Bourdieu 2003) during the early stages of the national education system. A content-oriented analysis of the paratexts and superstructure of three school grammars published between 1846 and 1865 is carried out, complemented by documents from official periodical sources of the time. The results identify three central actions —demand, codification, and dissemination— that organize the relationships established within the emergent Chilean grammatical-pedagogical field and condition the content of the school grammars in connection to the general process of linguistic standardization by the State.